2011
DOI: 10.1161/circulationaha.111.043851
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Activity With Vascular Endothelial Function and Intima-Media Thickness

Abstract: Background-Impairment of vascular endothelial function and increased intima-media thickness (IMT) are important early steps in atherogenesis. Longitudinal data on the effect of physical activity on endothelial function and IMT in healthy adolescents are lacking. We investigated prospectively the association of leisure-time physical activity with endothelial function (brachial artery flow-mediated dilatation; FMD) and aortic IMT in adolescents. Methods and Results-FMD and IMT were measured with ultrasonography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
120
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 49 publications
4
120
4
1
Order By: Relevance
“…Physical activity has been related to decreased progression of arterial IMT during adolescence, independent of inflammation. 8 Recent data have shown that xxx Q12 results in greater nitric oxide release because of wall shear stress and stimulates arteriogenesis and endothelial repair. 26 This protective effect of exercise on vascular structure may be boosted by maturational events, because it seems to be maintained into later life independent of patterns of physical activity in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity has been related to decreased progression of arterial IMT during adolescence, independent of inflammation. 8 Recent data have shown that xxx Q12 results in greater nitric oxide release because of wall shear stress and stimulates arteriogenesis and endothelial repair. 26 This protective effect of exercise on vascular structure may be boosted by maturational events, because it seems to be maintained into later life independent of patterns of physical activity in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Its prolonged practice has been linked to the control the progression of intima-media thickness (IMT) in hypertensive adults 6 and also in healthy adolescents. 7,8 Recently, studies have reported that behavioral variables can modulate the relationship between the progression of artery IMT and its risk factors. 9,10 For instance, smoking exacerbates the relationship between age and the metabolic syndrome components and age and carotid IMT (cIMT) in young adults.…”
Section: Q5mentioning
confidence: 99%
“…22,23) Moreover, walking is the preferred physical activity at home after hospital discharge for elderly patients because it requires no special exercise equipment. Increased time spent in moderate-intensity physical activity is associated with increased high-density lipoprotein levels, 24) lower levels of inflammatory markers (eg, tumor necrosis factor alpha, C-reactive protein, and interleukin-6), 25) increased vascular endothelial function, 26) and decreased progression of intima-media thickness. 26) Collectively, improved walking speed during hospitalization might lead to the maintenance of a fast walking speed in activities of daily living after hospital discharge, which might induce a cycle of increased physical activity that has a direct effect on cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective observational studies have demonstrated an association between reduced carotid and aortic IMT and increased leisure physical activity 18 and aerobic fitness, 19 respectively, in healthy Finnish adolescents. Our data corroborate the findings of an intervention study involving obese children, in which a reduction in CCA-IMT was observed after 12 weeks of exercise, even in the absence of significant changes in C-reactive protein or triglyceride levels.…”
Section: 1517mentioning
confidence: 99%